2018
DOI: 10.1111/dme.13841
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Quality of Life Inventory (PedsQL) 3.2 Diabetes Module for youth with Type 2 diabetes: reliability and validity

Abstract: Aim To test the measurement properties of the revised and updated Pediatric Quality of Life Inventory (PedsQL) 3.2 Diabetes Module originally developed in Type 1 diabetes in youth with Type 2 diabetes. Methods The PedsQL 3.2 Diabetes Module and PedsQL Generic Core Scales were administered in a field test study to 100 young people aged 9–25 years with Type 2 diabetes. Factor analysis was conducted to determine the factor structure of the items. Results The 15‐item Diabetes Symptoms Summary Score and 12‐item Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Therefore, we compiled PedsQL scores from published datasets in which similar age of inclusion criteria was implemented. Raw PedsQL score data from healthy controls, type 1 (T1D) and type 2 diabetes (T2D) (Varni et al, 2019 ), intellectual disability (ID) (Kilincaslan et al, 2019 ), and idiopathic autism (Stokes et al, 2017 ) were utilized as comparative assessment metric. For ease of interpretability, our PMD, RTT, and SYNGAP1- ID data were aggregated to create a new syndromic ASD cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we compiled PedsQL scores from published datasets in which similar age of inclusion criteria was implemented. Raw PedsQL score data from healthy controls, type 1 (T1D) and type 2 diabetes (T2D) (Varni et al, 2019 ), intellectual disability (ID) (Kilincaslan et al, 2019 ), and idiopathic autism (Stokes et al, 2017 ) were utilized as comparative assessment metric. For ease of interpretability, our PMD, RTT, and SYNGAP1- ID data were aggregated to create a new syndromic ASD cohort.…”
Section: Resultsmentioning
confidence: 99%
“…PedsQL 4.0 scores were compiled from published datasets in which similar age of inclusion criteria was implemented. Raw PedsQL 4.0 score data from healthy controls, type 1 (T1D) and type 2 diabetes (T2D)[18], intellectual disability (ID)[19], and idiopathic autism[12] were utilized as comparative assessment metric. For ease of interpretability, our PMD, RTT, and SYNGAP1- ID data were aggregated to create a new syndromic ASD cohort.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the PedQL TM 4.0-GCS was used to evaluate the quality of life of children with diabetes mellitus, and the total score was found to be lower than that of healthy children (2). Similarly, the scales have been widely utilized in the evaluation of other pediatric diseases, such as diabetes (9), cancer (10), and systemic lupus erythematosus (SLE) (11), and the results suggest that the quality of life of children with chronic diseases is generally low (12).…”
Section: Discussionmentioning
confidence: 98%
“…PNS is a prolonged and recurrent condition requiring longterm therapy with steroids and other immunosuppressive agents, and children are primarily cared for at home, rather than in the hospital. Previous studies have shown that chronic diseases in children have a significant negative impact on growth, involvement in social activities, psychological wellbeing, and other aspects related to quality of life (1)(2)(3). PNS is a disease with a long duration and frequent recurrences, with a diverse range of causes that vary from person to person.…”
Section: Introductionmentioning
confidence: 99%